Stability assessment of limestone cave: Batu Caves, Selangor, Malaysia - Lai, G.T. (Penerbit Universiti Kebangsaan Malaysia, 2018)
The limestone hill of Batu Caves is slowly being turned into a recreation park for slope climbing, base jumping and cave exploring. Quantitative assessment on the stability of the cave is essential to ensure the safety of tourists and visitors. The aim of this study was to quantitatively assess the stability of Gua Damai, Batu Caves, Selangor, Malaysia by using the Q system for rock mass classification, together with other factors such as cave width and thickness of the cave roof. The stability of the limestone cave wall was evaluated using Slope Mass Rating (SMR). A discontinuity survey conducted along the slopes beneath the opening of the cave showed that the rock mass comprised of four major joint sets labeled as J1, J2, J3, and J4 with the dip directions and angles of 110/73, 325/87, 243/39 and 054/30, respectively. The result of kinematic analysis showed that the dip direction/dip angle of a potential wedge failure was 051/59. By referring to the ratio of cave roof thickness with cave width, the results showed that the cave is stable. Based on the relationship between Q system and the cave width, the stabilities of Section 4 of Gua Damai is stable while Section 1, 2, 3, 5, 6, 7 and 8 require supports. Based on SMR, the cave walls stability at Portion c, d, and f were not stable while Portion a, b, e and g were stable. Overall, the most stable part of the cave is Section 4 followed by Sections 5 and 2. Sections 1, 3 and 8 are moderately stable while Sections 6 and 7 have poor stability.